Disinfection options for irrigation water: Reducing the risk of fresh produce contamination with human pathogens. Issue 20 (17th October 2020) - Dandie, Catherine E.; Ogunniyi, Abiodun D.; Ferro, Sergio; Hall, Barbara; Drigo, Barbara; Chow, Christopher W. K.; Venter, Henrietta; Myers, Baden; Deo, Permal; Donner, Erica; Lombi, Enzo
Abstract: The growing health and economic burden posed by foodborne pathogens has stimulated global interest in the development of safe, affordable, effective and environmentally-sustainable irrigation water treatment technologies. This review critically compares the potential of existing and emerging methods for disinfection of irrigation water to reduce pathogenic microbial loads on high-risk vegetables and minimally processed fresh produce. We explore electrochemical disinfection and electrolyzed oxidizing water as alternatives to traditional chlorination, and identify hydrodynamic cavitation as an emerging disinfection strategy worthy of further investigation in this context. In addition, we assess the state of the knowledge regarding the impact of current water sanitation strategies on the ecological dynamics of plant and soil microbes and the potential induction of viable but nonculturable cells. Increased research in these areas could translate into substantial improvement in the overall quality and value of fresh produce, while maintaining environmentally-sustainable irrigation water usage. Graphical Abstract: UF0001